Analisis Model Altman Z”-Score Sebagai Prediksi Kebangkrutan - Rivka Izzati Nisa; Chasan Azari; Winarto (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2024)
The retail business is a great opportunity for Indonesia because some people earn income from selling retail goods, but in recent years retail companies in Indonesia have experienced a slowdown, impacting many large and well-known retail outlets in Indonesia that have begun to stop their business for various reasons. Increasingly sophisticated technological developments such as the emergence of e-commerce that is more attractive to buyers because of the ease of transacting at a much more affordable price is one of the reasons. This study aims to analyze the prediction of potential bankruptcy in retail subsector companies on the Indonesia Stock Exchange for the 2018-2021 period by applying the Altman Z